Decolonizing Design : A Cultural Justice Guidebook - Tunstall, Elizabeth (Dori) (Cambridge : The MIT Press, 2023)
Illustrations by Ene Agi
A guidebook to the institutional transformation of design theory and practice by restoring the long-excluded cultures of Indigenous, Black, and People of Color communities. From the excesses of world expositions to myths of better living through technology, modernist design, in its European-based guises, has excluded and oppressed the very people whose lands and lives it reshaped. Decolonizing Design first asks how modernist design has encompassed and advanced the harmful project of colonization—then shows how design might address these harms by recentering its theory and practice in global Indigenous cultures and histories. A leading figure in the movement to decolonize design, Dori Tunstall uses hard-hitting real-life examples and case studies drawn from over fifteen years of working to transform institutions to better reflect the lived experiences of Indigenous, Black, and People of Color communities. Her book is at once enlightening, inspiring, and practical, interweaving her lived experiences with extensive research to show what decolonizing design means, how it heals, and how to practice it in our institutions today. For leaders and practitioners in design institutions and communities, Tunstall's work demonstrates how we can transform the way we imagine and remake the world, replacing pain and repression with equity, inclusion, and diversity—in short, she shows us how to realize the infinite possibilities that decolonized design represents.(from publisher)
boek